Efeito do extrato aquoso de Mimosa setosa Benth. var. paludosa Benth. Barn. (Fabaceae) sobre Drosophila melanogaster (diptera - drosophilidae) - SOUZA, Amanda Costa de (2022)
Plants have mechanisms of physical and chemical defense, among the chemical defenses the secondary metabolites stand out. The use of these compounds through plant extracts is a practice that has been resumed in integrated pest management. Mimosa setosa Benth. var. paludous Benth. Barn., Is a weed that may present insecticidal potential. The objective of this study was to investigate the bioactivity of aqueous extracts obtained from leaves and fruits of Mimosa setosa on Drosophila melanogaster (Meigen, 1830). Hoping to contribute to possible agricultural improvements by providing subsidy for the subsequent development of insecticides. Bioassays were performed with dry and fresh plant material at concentrations of 25%, 50% and 100%. Drosophila melanogaster larvae were placed in test tubes with the culture environment ontaining the extracts to be checked. The parameters analyzed were survival and rate of development. Statistical analyzes were performed with the aid of the Past 2.17 program. To analyze the normality and the homoscedasticity of the data the Shapiro-Wilk and Levene tests were used respectively. For the data that presented normal distribution and homoscedasticity, we used the parametric method (ANOVA and Tukey for comparison of means by pair). When the ANOVA assumptions were not met, the non-parametric method (Kruskal-Wallis medians, as well as Dunn's tests) was used. The confidence interval was 5% for all tests. In general, the extracts did not present significant effects on the survival and rate of development.